Determination of Cd(II) by FAAS in Turkish Cigarette Tobacco: A Pre-Concentration Procedure with Diethyldithiocarbamate Immobilized Amberlite XAD-2 Resin - Fatma Aygun, Seker; Caner Ustaosman, Basak; Karacan, Meral (Asian Journal of Chemistry, 2011)
A simple and rapid procedure for the pre-concentration of Cd(II) in Turkish cigarette tobacco was developed. Present Cd(II) in the tobacco samples was pre-concentrated by sodium diethyldithiocarbamate immobilized Amberlite XAD-2 resin and determinations were carried out by using flame atomic absorption spectrometry. Parameters such as the effects of pH, nitric acid concentration and flow rate on the pre-concentration procedure were investigated. A preconcentration factor of 100 was achived by employing optimum conditions. The calibration plot for Cd(II) was linear in 0.1-2.0 mg mL-1 concentration range with the detection limit of 0.03 mg mL-1 and the relative standard deviation (RSD) was 2.3 % for the overall procedure (n = 6). The accuracy of the proposed procedure was evaluated by means of cadmium determination in certified reference oriental tobacco leaves (CTA-OTL-1). The result obtained was in good agreement (1.07 ± 0.14 mg kg-1) with certified value (1.12 ± 0.12 mg kg-1). The procedure was applied to the determination of Cd(II) in cigarette tobacco samples. The concentration of Cd(II) in the two cigarettes tobacco samples was determined as 2.5 and 2.8 mg kg-1, respectively.